MEMBANGUN KETERAMPILAN PROSES SAINS MAHASISWA PADA MASA PANDEMI MELALUI CHEMISTRY HOME EXPERIMENTS - Munasprianto Ramli; Buchori Muslim; Anggit Refo Kurniawan (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2022)
The Covid-19 pandemic that has occurred since the beginning of 2020 has caused chemistry practicum in the laboratory, which is an important part of learning chemistry, to not be carried out during the covid 19 pandemic. The purpose of this study is to analyze how the Chemistry Home Experiment builds science process skills during the pandemic. This research method is a mix method with a convergent design approach. The participants of this research were 96 first year students of chemistry education at UIN Syarif Hidayaullah. The instrument used in this study was an observation sheet consisting of 20 indicators from aspects of science process skills and documentation in the form of practicum videos and practicum reports. Analysis of the data using content analysis quantitatively and qualitatively. The results showed that aspects of science process skills that received very good predicates were aspects of observing/observing, aspects of grouping/classifying, aspects of using tools and materials, aspects of applying concepts and aspects of communicating. Aspects of interpreting and aspects of predicting received good predicates. As for the aspect that gets the predicate less is the hypothesis. Based on these results. From these studies and observations, it can be concluded that the Chemistry Home Experiment can build students' science process skills in learning basic chemistry during the pandemic.